Electronic eye for visually impaired - Yeo, Kai Yeat (2018)
With an estimated number of 253 million people in the world that are lawfully certified as either Visually Impaired or blind. Visually Impaired means that the personnel does not have vision that are treatable with accessories such as spectacles or contact lenses. While it the severity of the challenges caused by the impairment might differ from individuals, they are still met with some sort of difficulty daily, ranging from the inability to recognize what or who is in front of them, the non-verbal expression of the people they are interactive with, and the inability to read text on printed media. With the high number of people facing certain difficulty due to this impairment, there is growing concern and efforts in attempts to help improve the daily lives of these people. Although there are commercial products available to assist with the challenges, it can be very expensive for the average person. To develop a solution that is much more accessible and relatively affordable, this project aims to build a prototype as a Proof of Concept, by using a device based on a small form factor computer with a camera. A device that will function as the Electronic Eye for the Visually Impaired. The processor is implemented with community made libraries related to image analytics to perform predictions to recognize objects, known faces, and expressions in an image captured by the camera, which are factors that the Visually Handicapped wish to identify. The aim of the prototype is to show that it is possible to create a device by using readily available libraries, tools and affordable small form factor computers, increasing the availability and lower the cost for such visual aid tool to be developed for the Visually Impaired, which can in turn help improve their quality of life.